Identitetens Etablering Og Opløsning I Stig Dalagers Romanbiografi Det Blå Lys - Cymbrykiewicz, Joanna (Folia Scandinavica Posnaniensia, 2014)
The article features the issue of identity building and disintegration as it appears in Stig Dalager’s biographical novel on Marie Curie, Det blå lys (The Blue Light) from 2012. It also discusses the problem of the narrator’s (and hence the author’s) presence in the text, which makes one dwell on the biography’s actual role in contemporary literary practice. The article’s stance is that biographies, including biographical novels, are typically produced with the contemporary reader and his expectations in mind. That is the reason why they focus on these issues in the protagonist’s life that may be of universal interest and not necessarily reflect the depicted person’s actual experience. As the novel communicates a postmodern view on human life, it is identity and problems with its establishment and disintegration that seem to be central for the work’s expression. In order to illustrate the process of identity building and deconstruction three key aspects in the protagonist’s life have been chosen for a closer inspection: the national, the feminine and the professional. The analysis shows that identity, as described in the novel, is a volatile and changeable phenomenon which is constantly transformed and redefined and thus can never be preserved and seen as a monolith. In order to discuss the above mentioned issues some ideas of Hayden White and Zygmunt Bauman have been used.